P14 Acute management of traumatic anterior shoulder dislocations during COVID-19: are we meeting published national standards for treatment during the pandemic?. (8th April 2021) - Donovan, Richard L; Abdelmalek, Amir; Crowther, Mark A A; Packham, Iain
Abstract: Background: BESS/BOA Patient Care Pathways provide national guidelines for acute management of traumatic anterior shoulder dislocations with respect to emergency reduction and clinic follow-up. COVID-19 posed challenges in terms of analgesia choice for reductions and altered follow-up arrangements. This study aimed to assess variance from the care pathway. Methodology: We performed a retrospective case note analysis of all emergency presentations with acute traumatic anterior shoulder dislocations at the MTC in Bristol. We compared 01 Apr to 31 May in 2019 to the same period in 2020 to analyse the effects of the COVID-19 pandemic on the management of these injuries. Data parameters collated included examinations and imaging pre- and post-reduction, choice of analgesia, follow-up rates, referral to physiotherapy, and further imaging requested. Results: We identified 32 patients in 2019, and 24 in 2020. Use of Entonox fell during the pandemic in favour of Penthrox. Use of conscious sedation (requiring full PPE) remained around 20%. Pre- and post-reduction orthogonal radiographs was near 100% in both cohorts. Referral to follow-up was 88% in 2019 but fell to 38% in 2020. Of those assessed in clinic during COVID-19, fewer were mobilised early or referred to outpatient physiotherapy compared to the previous year. Conclusions: The acute management of anterior shoulder dislocations during the early COVID-19 pandemic faced two main challenges: choice of suitable analgesia whilst minimising AGPs; and limiting access to 'face-to-face' follow-up to minimise hospital attendances. A key concern was a significant decrease in patient follow-up, thus limiting the access to optimal aftercare such as physiotherapy and further imaging.